Strategizing Education: Ecosystem Transition - Lidia V. Kremneva; Kirill E. Zavedensky; Pavel D. Rabinovich; Svetlana N. Apenko (National Research Mordova State University, 2020)
Introduction. The authors of the article, based on numerous studies on the transformation of the education system, offer a practical model of education, developed with reference to a view of education from a constructed image of the future, as well as to global trends. The essential basis of the model are productive processes of education and social engineering, as well as the folding of the ecosystem with the value-normative basis for matching the educational needs of different stakeholders of educational activities. The relevance of the article is determined by the need to respond to the discrepancy with the world trends of the education system, formed to ensure the reproduction of existing cultural norms and socio-productive relations in society in order to maintain its stability. The aim of the study is to develop an educational model, the key form of organization of which is the educational ecosystem. The model content is formed as a reflection of the process of strategizing based on the fundamental development trends. Materials and Methods. Using analysis and synthesis methods, groups of topical world trends are identified and their impact on the projected image of education is shown. Methods of focus groups and case studies are utilized to study advanced educational practices. Hypotheses on the projected educational model are generalized and advanced. The hypotheses are tested. The elements of the new model of education proposed by the authors are tested. Results. The authors substantiated the concept of a new model of education as a result of value and semantic bases of strategy of consent of different social groups participating in the process of education. Methodological approach to education development strategy as if looking from the future differs from the dominant methodological method of future formation by means of its present modification and reworking. The authorʼs concept of the model of education from the future rests on the value and meaning foundation, which distinguishes it from the dominant position associated with the justification of only requirements to learning outcomes and content of education. The new vision of "education from the future" will contribute to the successful implementation of practices of transformation of education taking into account global trends based on the vision of education from the future, namely, a collective-wanted image of the future, rather than a continued "reworkedˮ present. Discussion and Conclusion. This article is useful for organizers of changes in educational systems at different levels (region, city, secondary school), as well as for researchers in the field of modern models, approaches and educational technologies that arise under the influence of global trends.